Desafios da gestão sustentável em meios de hospedagem: um estudo multicasos no Litoral Norte do estado de SP - João, Cristina de Moura (2014)
This research aims to analyze how lodging facilities can contribute to the promotion of sustainable actions in their supply chain. According to previous studies, hotels and others lodgings managed to influence their suppliers to adopt sustainable practices in their processes. Thus were listed the following specific objectives: to verify sustainable actions in the lodging facilities (in social, economic and environmental sphere) and identify which one there are more actions and activities; analyze the reasons that led them to adopt such practices and which benefits they can reach; and also analyze difficulties in performing sustainable actions and, finally, to examine whether this actions influence other parts of the lodging supply chain to adopt sustainable practices. For this purpose, the following concepts will be explained: sustainable development; tourism, passing by mass and sustainable tourism and also how they can relate; tourism supply chain and its possible representations, and finally, lodging facilities and their classifications in Brazil. The research strategy applied was case study, using within-case analysis as a method. This study was conducted at Sao Paulo’s North Coast, which includes Ubatuba, Caraguatatuba, São Sebastião and Ilhabela cities. The study found that the lodging facilities in this region perform some sustainable practices, and most of it falls on the environmental dimension. However, these practices are still very incipient and made without technical support. On the influence of the supply chain, it was found that most managers do not thought about extending this sustainable practices to suppliers. The ones who considered this possibility claim that lack the size needed. In other words, companies researched are small and medium-sized and they cannot put pressure on its stakeholders. Therefore, it can be said that even in a coastal area where the main activity is tourism - and the attractions are natural beauties that need to be preserved - sustainable development is still an issue that needs to be understood, disseminated and encouraged.